Different configurations of SARS-CoV-2 spike protein delivered by integrase-defective lentiviral vectors induce persistent functional immune responses, characterized by distinct immunogenicity profiles - Borghi, Martina; Gallinaro, Alessandra; Pirillo, Maria Franca; Canitano, Andrea; Michelini, Zuleika; De Angelis, Maria Laura; Cecchetti, Serena; Tinari, Antonella; Falce, Chiara; Mariotti, Sabrina; Capocefalo, Antonio; Chiantore, Maria Vincenza; et al. (Frontiers in Immunology, 2023)
Several COVID-19 vaccine strategies utilizing new formulations for the induction of neutralizing antibodies (nAbs) and T cell immunity are still under evaluation in preclinical and clinical studies. Here we used Simian Immunodeficiency Virus (SIV)-based integrase defective lentiviral vector (IDLV) delivering different conformations of membrane-tethered Spike protein in the mouse immunogenicity model, with the aim of inducing persistent nAbs against multiple SARS-CoV-2 variants of concern (VoC). Spike modifications included prefusion-stabilizing double proline (2P) substitutions, mutations at the furin cleavage site (FCS), D614G mutation and truncation of the cytoplasmic tail (delta21) of ancestral and Beta (B.1.351) Spike, the latter mutation to markedly improve IDLV membrane-tethering. BALB/c mice were injected once with IDLV delivering the different forms of Spike or the recombinant trimeric Spike protein with 2P substitutions and FCS mutations in association with a squalene-based adjuvant. Anti-receptor binding domain (RBD) binding Abs, nAbs and T cell responses were detected up to six months from a single immunization with escalating doses of vaccines in all mice, but with different levels and kinetics. Results indicated that IDLV delivering the Spike protein with all the combined modifications, outperformed the other candidates in terms of T cell immunity and level of both binding Abs and nAbs soon after the single immunization and persistence over time, showing the best capacity to neutralize all formerly circulating VoC Alpha, Beta, Gamma and Delta. Although present, the lowest response was detected against Omicron variants (BA.1, BA.2 and BA.4/5), suggesting that the magnitude of immune evasion may be related to the higher genetic distance of Omicron as indicated by increased number of amino acid substitutions in Spike acquired during virus evolution.